OPTIMIZATION OF THE BEHAVIOR OF HEALTH PERSONNEL DOMAIN ON COVID-19 PREVENTION IN CIKETING UDIK PUSKESMAS BANTARGEBANG BEKASI CITY - Kurniati Nawangwulan; Ady Purwoto (International Journal of Health Science & Medical Research, 2022)
The state of Indonesia has data on the prevalence of COVID-19 sufferers based on data released by the Covid-19 emergency hospital until October 28, 2020, the total number of COVID-19 patients is 2,240 people. These health workers are known to be infected while treating and handling Covid-19 patients and some are infected from the community, work environment and their family members. This research uses descriptive statistical analysis method with a case study approach using Pearson correlation test and distributing questionnaires to 40 respondents of health workers at Ciketing Udik Health Center Bantargebang Bekasi City, the sample method uses total sampling. The research stage is to conduct a survey with a questionnaire with the aim of analyzing the optimization of the behavioral domain of health workers for the prevention of COVID-19. The results of the research are optimizing the behavior of health workers at the Ciketing Udik Health Center in preventing covid-19 by using masks at all times, using complete PPE when performing services, washing hands for at least 20 seconds, hand sanitizer, consuming healthy foods such as vegetables, fruits and vegetables. fruits that contain high vitamin C, eggs, fish, lean meat and drink lots of water every day.